Number of cells in parathyroid tissue in primary hyperparathyroidism cases and its relationship with serum calcium value - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Background: The relationship between serum calcium (Ca) level to serum parathyroid hormone (PTH), phosphorus (P) levels and tissue properties of the parathyroid gland is unknown in primary hyperparathyroidism cases. Revealing this relationship may be useful for understanding the etiopathogenesis of primary hyperparathyroidism and determining the time of treatment. Methods: Ninety patients (71 females, 19 males, age range; 27-73 years, average age; 46) who underwent single gland excision with the diagnosis of primary hyperparathyroidism were studied. The patients were divided into 2 groups as serum Ca level <12 and serum Ca level >= 12. Age and sex of the patients, mean cell number of the gland, mean volume of the gland, serum levels of PTH, P, and histopathologic type of hyperplasia were evaluated. Results: The mean cell number per cubic centimeter is 22.9 (10-220 range) million in all glands. Serum Ca level was <12 in 82 (91.1%) of the patients, and >= 12 in 8 (8.9%) cases. Mean cell number of the gland, mean volume of the gland, existence of cystic hyperplasia of the gland, serum levels of PTH and P were statistically significant between the 2 groups (P < .001, P < .001, P < .05, P < .001, P < .05 respectively). Conclusion: In primary hyperparathyroidism cases serum Ca level is not related to age and sex but directly related to proportionals to the cell number and volume of the gland and serum levels of PTH, inversely related to cystic hyperplasia and serum levels of P. Early surgical intervention should be planned since the serum Ca level will be high in large adenomas with a noncystic radiological appearance.
Keywords: number of cells; parathormone; phosphorus; primary hyperparathyroidism; serum calcium; HYPOPARATHYROIDISM; EPIDEMIOLOGY; PREVENTION; MANAGEMENT